2023
DOI: 10.3390/antibiotics12040779
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Apis mellifera Bee Venom Collected in Northern Peru

Abstract: Due to the emergence of microorganisms resistant to antibiotics and the failure of antibiotic therapies, there is an urgent need to search for new therapeutic options, as well as new molecules with antimicrobial potential. The objective of the present study was to evaluate the in vitro antibacterial activity of Apis mellifera venom collected in the beekeeping areas of the city of Lambayeque in northern Peru against Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. Bee venom extraction was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…Pérez-Delgado et al [60] evaluated the antibacterial activity of Apis mellifera venom against E. coli, P. aeruginosa, and S. aureus. The outcome of their study showed the minimum inhibitory concentration (MIC) of 6.88 µg/mL against E. coli with no satisfactory results against P. aeruginosa, and S. aureus.…”
Section: Molecular Dynamics (Md) Simulationmentioning
confidence: 99%
“…Pérez-Delgado et al [60] evaluated the antibacterial activity of Apis mellifera venom against E. coli, P. aeruginosa, and S. aureus. The outcome of their study showed the minimum inhibitory concentration (MIC) of 6.88 µg/mL against E. coli with no satisfactory results against P. aeruginosa, and S. aureus.…”
Section: Molecular Dynamics (Md) Simulationmentioning
confidence: 99%
“…A series of recent studies indicated that BV has a wide range of microbial activity against bacteria, fungi, and viruses ( El-Didamony et al, 2022b ; Pérez-Delgado et al, 2023 ), as well as treating different types of cancer cells ( Taher et al, 2017 ; El-Didamony et al, 2022a ). Overall, BV and its selective components are considered promising agents for disease management.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of potential benefits from the combination between frankincense oil and the tested antibiotics is discouraging; however, the in vivo results allow us to suggest that the oil, per se, may act as a modulator of inflammatory responses in infectious diseases. Another interesting study by Pérez-Delgado [ 18 ] explored the in vitro antibacterial activity of Apis mellifera, venom collected from bees of Lambayeque, northern Peru, against E. coli , Pseudomonas aeruginosa , and Staphylococcus aureus reference strains. Three peptides of low molecular weights (5 kDa, 6 kDa, and 7 kDa) were separated from the crude bee venom.…”
mentioning
confidence: 99%